Rates of Evolution of Developmental Changes in Gene Expression in Sordariomycetes - Wang, Yen-Wen; Wang, Fen; Meng, Guoliang; Lopez-Giraldez, Francesc; Dong, Caihong; Wang, Zheng; Townsend, Jeffrey P (Molecular biology and evolution, 2025)
The phenotype of an organism is shaped by gene expression within developing tissues. This shaping relates the evolution of gene expression to phenotypic evolution, through divergence in gene expression and consequent phenotype. Rates of phenotypic evolution receive extensive attention. However, the degree to which divergence in the phenotype of gene expression is subject to heterogeneous rates of evolution across developmental stages has not previously been assessed. Here, we analyzed the evolution of the expression of single-copy orthologs within 9 species of Sordariomycetes Fungi, across 9 developmental stages within asexual spore germination and sexual reproduction. Rates of gene expression evolution exhibited high variation both within and among developmental stages. Furthermore, rates of gene expression evolution were correlated with nonsynonymous to synonymous substitution rates (dN/dS), suggesting that gene sequence evolution and expression evolution are indirectly or directly driven by common evolutionary forces. Functional pathway analyses demonstrate that rates of gene expression evolution are higher in labile pathways such as carbon metabolism, and lower in conserved pathways such as those involved in cell cycle and molecular signaling. Lastly, the expression of genes in the meiosis pathway evolved at a slower rate only across the stages where meiosis took place, suggesting that stage-specific low rates of expression evolution implicate high relevance of the genes to developmental operations occurring between those stages.